ナンキョク ヒョウショウ ノ コトナッタ タイセキ カンキョウ ニ オケル セキセツ ノ サンソ ドウイタイ プロファイル - 上田, 豊; アゲタ, ユタカ; 神山, 孝吉; カミヤマ, コウキチ; 成田, 英器; ナリタ, ヒデキ; 佐藤, 和秀; サトウ, カズヒデ; Ageta, Yutaka; Kamiyama, Kokichi; Narita, Hideki; Satow, Kazuhide (1991)
P(論文) 斜面下降風の卓越した地域と内陸高原ドーム域および両者の遷移帯における積雪の酸素同位体組成の垂直プロファイルを比較し, それぞれのプロファイルと各地域の堆積環境の特性をのべる。試料は, みずほ基地(高度2230m)の101本雪尺列にそった幅10m, 深さ1mのトレンチ, 前進拠点(3198m)の3m深雪穴, ドームキャンプ(3761m)の5m深雪穴から得た。試料の年代は, みずほ基地では雪尺測定値, 前進拠点とドームキャンプとではトリチウム濃度と総ベータ線量のピーク位置から求めた。斜面下降風域では雪の削はく・再堆積が起こりやすいため, 積雪の酸素同位体組成の経年変化は内陸ドーム頂部に近いほど良く保存される。ドームキャンプのプロファイルは, 南極点上空5000gpmにおける夏の気温の経年変化とよい相関にある。これは夏の気象状態が, 堆積後の蒸発・昇華による積雪表層の同位体組成の遷移に強く影響した結果と考えられる。 Vertical profiles of oxygen isotopic contents in deposited snow were obtained in the region where katabatic winds prevail (Mizuho Station : 70.7°S, 44.3°E, 2230m), the inland dome-like plateau (Dome Camp : 77.0°S, 35.0°E, 3761m) and the transitional zone between them (Advance Camp : 74.2°S, 35.0°E, 3198m). At Mizuho Station, the δ^<18>O contents have high values around the hiatus layers. However, synchronous relations cannot be found between the neighboring profiles, since snow was exchanged due to deposition and erosion by strong winds. Inter-annual variations of oxygen isotopic contents in snow have been preserved better in the inner parts of the ice sheet between the three zones observed in this study. The profile at Dome Camp has good correlation with the inter-annual variation of summer temperature at 5000gpm above the South Pole. This result suggests that the temperature at this level above the South Pole is representable for air temperature condition over the inland ice sheet, and the meteorological conditions in summer have a strong effect on the transition of the oxygen isotopic content of snow after deposition due to evaporation-sublimation. departmental bulletin paper